Age in the working life - A comparative study between the Swedish and the American labor markets - Paradis,Tim (2012)
Everyone has an age that whether we like it or not increases and also influences us differently in various situations in our society depending on our current age. In today’s media, the high unemployment rate amongst younger individuals has been mentioned as Sweden’s main social problem, which made me interested in investigating the importance of age through the working life in the labor markets. My bachelor thesis is characterized by a comparative study between the Swedish and the American labor markets. This should be viewed to broaden the discussion and make me able to see similarities and differences between two very different labor markets and legal systems. The history behind the development of the two countries’ later industrial relations are described, and then I proceed to explain the current situation and the influencing actors in the labor markets. Furthermore, I describe what age is and what age discrimination means for these two labor markets. Once this needed knowledge has been given, I discuss age importance through the working life. I describe the situations and laws that favor or disfavor younger or older individuals on the two labor markets. The focus is situations and regulations connected to when we enter the labor markets, while we have a job and finally when we leave the labor markets. Finally, the discussion about the various questions for this research is clarified, and if everyone should be considered to have an equal opportunity for labor market success, and whether younger or older have a stronger position on todays’ labor markets.
Keywords: Dagens arbetsmarknad; Arbetsmarknadsrelationer; Diskriminering; Ålder; Åldersdiskriminering och Ungdomsarbetslöshet. Discrimination; Industrial relations; Today’s labor market; Age; Age discrimination; and Youth unemployment.